THE FEAR OF DISHARMONY IN POLISH FOLK LITERATURE OF THE 19TH CENTURY AND THE BEGINNING OF THE 20TH CENTURY AS EXEMPLIFIED IN THE BELIEFS RELATED TO CHANGELINGS - Piotrowski, Robert Piotr (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The article focuses on the category of disharmony defining the beliefs about the nether world which functioned in folk culture of the 19th century and the beginning of the 20th century. The notion of harmony used herein refers to deviations from the sanctioned norm concerning the body and psychosomatic expressions. The analysis will center on beliefs related to changelings. These beliefs in turn will serve as a basis for defining the fear of otherness perceived as expressions of non-reality/the nether world.